Problems of diagnosing acute genital Lipschutz ulcer. Description of a clinical case and review of the literature - Briukhan, Sofiia; Kurochka, Valentyna (The Ukrainian Scientific Medical Youth Journal, 2025)
acute genital Lipschutz ulcer (AGLU) is a rare disease that usually occurs in girls who are not sexually active. In children, it often occurs as an emergency and remains a diagnostic problem for pediatricians, gynecologists and dermatologists. It is also extremely important to differentiate AGLU from sexually transmitted ulcers, such as syphilis and genital herpes. The etiology of GGVL is unknown, but recent studies have shown that it can be provoked by various infectious agents. Our goal is to supplement the literature and increase awareness of this unusual disease, as well as to consider a rapid diagnostic algorithm for timely detection and treatment. We conducted an analysis of domestic and foreign literature sources describing the appearance of lesions of the genital mucosa, which is preceded by flu-like symptoms. We also present a clinical case of an 11-year-old girl with a diagnosis of GGVL based on specific criteria, which include acute onset, exclusion of specific infectious and non-infectious causes, lack of previous sexual contact, and features of the ulcer. Treatment is mainly supportive with pain relief, but in case of multiple, large, or deep necrotic ulcers, local or short courses of systemic corticosteroids can be considered.